2009
DOI: 10.1590/s0004-27302009000800009
|View full text |Cite
|
Sign up to set email alerts
|

Prostate cancer and acromegaly

Abstract: Acromegalic patients have an increased prevalence of prostatic disorders compared to agematched healthy subjects. Increased size of the whole prostate or the transitional zone, together with an elevated incidence of other structural changes, such as nodules, cysts, and calcifications, have been reported. Prostate enlargement in young acromegalic patients with low testosterone levels due to central hypogonadism supports the hypothesis that chronic GH and IGF-I excess cause prostate hyperplasia. The relationship… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 56 publications
0
7
0
3
Order By: Relevance
“…The precise role(s) of these canonical GH response cis-elements in GH-dependent increase in ZEB2-NAT expression remains to be defined. In addition to the glomerular podocyte, our finding of GH-dependent increase in ZEB2 expression is also relevant to the role of GH in malignancies such as breast and prostate cancer wherein the GH/GHR axis has been demonstrated to play a permissive role (35). It is noteworthy that we were unable to verify expression of a closely related member of the ZEB family of protein, ZEB1 (␦EF1/ZFHX1A), in the podocyte (data not shown).…”
Section: Discussionmentioning
confidence: 74%
“…The precise role(s) of these canonical GH response cis-elements in GH-dependent increase in ZEB2-NAT expression remains to be defined. In addition to the glomerular podocyte, our finding of GH-dependent increase in ZEB2 expression is also relevant to the role of GH in malignancies such as breast and prostate cancer wherein the GH/GHR axis has been demonstrated to play a permissive role (35). It is noteworthy that we were unable to verify expression of a closely related member of the ZEB family of protein, ZEB1 (␦EF1/ZFHX1A), in the podocyte (data not shown).…”
Section: Discussionmentioning
confidence: 74%
“…The correlation between acromegaly and prostate cancer, until the present moment, is circumstantial. However, there is a correlation between serum levels of IGF-I at the upper limit of normality and prostrate cancer in the overall population (8,9).…”
Section: Introductionmentioning
confidence: 99%
“…This is a member of the kallikrein family of serine protease [31] and it is assumed that rising PSA levels during the natural history of PCa enhances the disease progression by proteolytically cleaving IGFBP-3, thereby increasing the amount of bioavailable IGF-1. [32] Previous study on Arab males indicated that IGF-1 and IGFBP-3 reached their peak levels during adolescence and gradually lowered with age. [33] IGFBP-3, the most prevalent form of the IGFBPs, has been linked with prostatic growth.…”
Section: Discussionmentioning
confidence: 99%